2022
DOI: 10.1002/jrs.6483
|View full text |Cite
|
Sign up to set email alerts
|

Tracking spatiotemporal evolution of cementitious carbonation via Raman imaging

Abstract: Carbonation of cementitious systems is an important phenomenon from both durability (rebar corrosion) and greenhouse emissions (CO2 sequestration) perspectives. Several analytical techniques are well‐established for measuring the kinetics of this dynamic phenomenon, ranging from measuring the pH change to quantifying the calcite content over time. However, the majority of these methods (with the exception of electron imaging) rely on bulk measurements which may miss the fine, microstructural changes that occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…The scattered light is analyzed by a spectrometer to obtain a Raman spectrum that shows the intensity of scattered light vs the shift of wavelength away from the excitation wavelength of the incident laser (Raman shift) . Previous studies have found Raman spectroscopy to be instrumental in studying cement clinker, mortars, the main hydration products, , alkali–silica reaction gels, , as well as cementitious pastes containing SCMs. Recently, Raman imaging has been successfully used to study and quantify phases in static systems such as anhydrous cements and aggregates, and dynamic systems such as cements undergoing hydration , and carbonation. In this study, the spectra obtained on a grid of points on a 5 mm × 5 mm area (spatial resolution: 1.25–10 μm) is analyzed and split into corresponding components and ultimately converted into binary phase images, where white denotes the presence and black denotes the absence of a mineral. We then obtained the PSDs from both the individual phase images (phase-specific PSD) and the composite phase images (overall PSD) using the procedure outlined in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…The scattered light is analyzed by a spectrometer to obtain a Raman spectrum that shows the intensity of scattered light vs the shift of wavelength away from the excitation wavelength of the incident laser (Raman shift) . Previous studies have found Raman spectroscopy to be instrumental in studying cement clinker, mortars, the main hydration products, , alkali–silica reaction gels, , as well as cementitious pastes containing SCMs. Recently, Raman imaging has been successfully used to study and quantify phases in static systems such as anhydrous cements and aggregates, and dynamic systems such as cements undergoing hydration , and carbonation. In this study, the spectra obtained on a grid of points on a 5 mm × 5 mm area (spatial resolution: 1.25–10 μm) is analyzed and split into corresponding components and ultimately converted into binary phase images, where white denotes the presence and black denotes the absence of a mineral. We then obtained the PSDs from both the individual phase images (phase-specific PSD) and the composite phase images (overall PSD) using the procedure outlined in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%